Analysis of a clinical case of a patient with a lymphedema of the right lower limb - I. G. Makarov; N. V. Makarova (Амбулаторная хирургия)
This clinical review describes  the patient’s  history of a third degree  lymphedema of the right lower extremity, who underwent  33 surgical interventions in the form of lipodermatofasciectomy, complicated  by frequent recurrent episodes  of erysipelas. The article describes  the tactics  of treatment and the specifics of the selection of knitwear for such a patient.